Inhibition of endothelial cell survival and angiogenesis by protein kinase A - Kim, Semi; Bakre, Manjiri; Yin, Hong; Varner, Judith A. (The Journal of Clinical Investigation, 2002)
Receptors for the provisional ECM are important regulators of angiogenesis. One of these receptors, integrin α5β1, plays a critical role in tumor- and growth factor–induced angiogenesis, because antagonists of this integrin potently inhibit angiogenesis and tumor growth. Here we show that the integrin α5β1 promotes endothelial cell survival during angiogenesis in vivo by suppressing the activity of protein kinase A (PKA). Antagonists of integrin α5β1 activate PKA, which then leads to the activation of caspase-8 and induction of apoptosis. Direct activation of PKA by cAMP or by expression of the PKA catalytic subunit also induces endothelial cell apoptosis, resulting in angiogenesis inhibition in vivo. Our studies indicate that ligation of integrin α5β1 during angiogenesis suppresses an apoptotic program that is dependent on PKA. These studies also indicate that induction of endothelial cell apoptosis in vivo by genetic or pharmacological activation of PKA may be a useful strategy to inhibit angiogenesis.